Hubungan Kekuatan Otot Tungkai, Koordinasi Dan Konsentrasi Terhadap Kemampuan Shooting Siswa Ekstrakurikuler Futsal Sma Negeri 3 Palopo - Ikhtiar Ghazaly; Rasyidah Jalil; Irsan Kahar; Rachmat Hidayat (Universitas Hamzanwadi, 2026)
The futsal shooting ability of students in the extracurricular program at Palopo State High School 3 remains low, presumably because their lower-body muscle strength, coordination, and concentration have not yet developed optimally. This study aims to analyze the relationship between lower-body muscle strength, coordination, and concentration and futsal shooting ability, both partially and simultaneously. This study employed a quantitative approach with a correlational design. A sample of 23 students was selected using total sampling. The instruments used were the standing broad jump test (lower limb muscle strength), the wall pass test (coordination), the grid concentration test (concentration), and the goal-shooting test. Data analysis included descriptive statistics, normality tests, linearity tests, Pearson Product-Moment correlation, and multiple correlation at a significance level of 0.05. Results: There was a significant positive relationship between lower limb muscle strength and shooting ability (r = 0.966; p < 0.001), coordination and shooting ability (r = 0.922; p < 0.001), concentration with shooting ability (r = 0.959; p < 0.001), and simultaneously, the three variables have a very strong relationship (R = 0.967; R² = 0.934; p < 0.001). Conclusion: Futsal shooting ability is influenced by the integration of physical, motor, and psychological factors. An integrated and balanced training program is recommended to improve students’ shooting ability.